Research note: Establishment of a multiplex PCR detection system for different infectious bronchitis virus strain genotypes in laying hens - Changjing Zhao; Cheng Yuan; Qingsen Zhao; Aihong Xia; Yaqing Dong; Shuying Xu; Shihan Chen; Yue Yuan; Yongjuan Wang (Poultry Science)
This study produced a method for the fast detection and identification of five strains of infectious bronchitis virus (IBV), including the currently prevalent wild-type QX and G Ⅵ-1 strains, in addition to the Mass, 4/91, and LDT3 strains that are used as vaccines. Based on the spike 1 (S1) glycoprotein gene sequences of the IBV Mass, QX, G Ⅵ-1, 4/91, and LDT3 strains, five sets of customized primers, showing excellent specificity, were designed and synthesized to target the appropriate conserved sequences. After repeated improvement, a multiple PCR detection approach with strong specificity for the simultaneous detection of IBV Mass, QX, G Ⅵ-1, 4/91, and LDT3 strains was initially established. The optimal final concentration of both upstream and downstream primers in this system was 0.1 μmol/L, with an annealing temperature of 58°C and a cycle number of 35. Specificity detection revealed high accuracy, as the approach was able to amplify the expected specific segments of each strain without cross-amplification. As templates for the sensitivity test, the recombinant plasmid standards were detected with a limit of 103 copies/μL or less. The results exhibited high sensitivity of this method. It was subsequently applied to the identification of purposefully randomly mixed infections of two, three, four or five IBV strains mentioned above in samples of chicken embryos. All of the intentionally infected samples showed the expected amplified bands. Using this technology, it was also possible to correctly identify suspected IBV infected chicken tissue samples and clinical pharyngeal and anal swab samples from different laying hen farms. To sum up, the multiple PCR detection method created in this work has good clinical application effects and provides a new technical way of quickly identifying and detecting five IBV strain genotypes.